Psychosocial Correlates of Sexual Harassment among Female Undergraduates in Ekiti State - Olubunmi, Mokuolu Bolade (Advances in Social Sciences Research Journal, 2019)
The contemporary complications of sexual harassment among females is at its alarming rate as each day unfolds, and as long as there are social interactions there will always be attractions, which may either lead to warm attention or harassment. This may be associated with fashion which is determined by people of different personality, the kind of natural body shape or self-structured body shape and self-esteem of individuals. This study examined the Psycho-social factors predicting sexual harassment among female undergraduates. Sexual harassment questionnaire, index of self-esteem and Big five personality inventory were employed for the study, though only two dimensions of personality (Extraversion and neuroticism) were considered. Six body shapes were also presented to the respondents to choose which of them actually describe their look; this was used to find out if body shapes could make an individual to be prone to sexual harassment. One hundred and four female undergraduates of Ekiti State University were randomly selected through cluster sampling. Three hypotheses were tested using Analysis of Variance. Result showed a significant main effect of self-esteem and also significant interaction effect of extraversion and self-esteem on sexual harassment. Place of abode has a significant effect on whether there will be sexual harassment or not, so also is family type. Respondents living with guardian reported the highest level of harassment, while those living with both parents reported the lowest level; those from polygamous family are significantly higher than those from monogamous family. Lastly Body shape has no significant effect on sexual harassment.